PENGUATAN SPIRIT DAKWAH SEBAGAI UPAYA MEWUJUDKAN DESA PRAGAAN DAYA UNGGUL DAN BERKARAKTER ISLAMI - Rosyidi, Rosyidi; Ariyah, Zulfiatul (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2024)
This community service activity was motivated by the declining spirit of da'wah and internalization of Islamic values in the social life of Pragaan Daya Village. Rapid social and economic development is not always accompanied by moral and spiritual strengthening, resulting in various problems such as declining religious participation, weak social awareness, and a lack of role models in community life. Therefore, efforts to strengthen the spirit of da'wah are needed as a strategy to build a superior, religious, and Islamic community. The community service methods used include a participatory and educational approach with several stages of activities, namely: (1) socialization of the importance of contextual and moderate da'wah, (2) training of village da'wah cadres for religious leaders, mosque youth, and Quran teachers, (3) community development through thematic recitations and religious social activities, and (4) da'wah assistance based on economic empowerment of the people. This approach was carried out collaboratively between the community service team, the village government, religious leaders, and local educational institutions. The results of the community service showed an increase in the community's understanding of Islamic values in daily life, the formation of the Pragaan Daya Village Da'wah Cadres, and increased community participation in religious and social activities. In addition, there is a growing collective awareness to make da'wah a social movement that promotes independence, brotherhood, and civilized village development. Thus, strengthening the spirit of da'wah has proven to be effective as a means of shaping Pragaan Daya Village to be superior and Islamic in character.